PEMETAAN KONDISI GEOGRAFIS DAN ASET DESA GARAWANGI KABUPATEN MAJALENGKA, UNTUK PERENCANAAN DESA BERKELANJUTAN - Lutfi Fais, M; Virgiawan, Muhammad; Septi Anggraini, Tania (PILAR, 2025)
This study aims to analyze the geographical conditions and village assets in Garawangi Village, Sumberjaya District, Majalengka Regency, as the basis for sustainable development planning. The research is motivated by the fact that Garawangi Village holds a strategic position for sustainable spatial development. The data used include high-resolution satellite imagery from SAS Planet, the National Digital Elevation Model (DEMNAS), and administrative boundary shapefiles of the village. The data processing method was carried out in three stages: topographic analysis (contours and slope gradients), land cover classification using the supervised classification method, and village asset mapping through geotagging techniques. The results of this study indicate that approximately 70% of the village area consists of flat land, around 20% is gently sloping, and the remainder is undulating, with an elevation ranging from 29 to 63 meters above sea level. Land cover is dominated by agricultural/plantation areas (about 60%), followed by tree vegetation, water bodies, built-up areas, and vacant land. Asset mapping shows that village facilities are concentrated in the settlement center.